Evaluasi Program Pendidikan Pemilih Berkelanjutan melalui Instagram Pascapemilu di KPU Kota Singkawang: Pendekatan Model CIPP - Ayu Gintari; Sitti Mania; Muhammad Nur Akbar Rasyid (Jurnal Global Futuristik, 2026)
Although social media has increasingly been utilized as a medium for voter education, studies evaluating its implementation during the post-election period remain relatively limited. This study aims to evaluate the Sustainable Voter Education Program conducted through Instagram by the Singkawang City General Election Commission (KPU) using the CIPP (Context, Input, Process, Product) evaluation model. The research employed a qualitative evaluative approach with data collected through interviews, observations, and documentation studies. Research informants consisted of the Chairperson of the Singkawang City KPU, Instagram administrators, content production staff, first-time voters, university students, Instagram followers, and representatives of youth communities. The findings indicate that, in the context dimension, the program was implemented in response to the community’s need for post-election information related to elections and democracy. In the input dimension, the program was supported by human resources, supporting facilities, planning mechanisms, and educational materials that referred to KPU regulations. In the process dimension, program implementation was carried out through structured stages of planning, content production, verification, and publication. In the product dimension, Instagram was able to reach a broad audience and received positive responses from users. Informants perceived the published content as relevant, easy to understand, and effective in enhancing public understanding of democracy and electoral issues. This study recommends increasing content innovation, optimizing Instagram’s interactive features, and expanding collaboration with various community groups to strengthen the implementation of sustainable voter education programs.